Ejection Fraction Recovery after Coronary Artery Bypass Grafting for Ischemic Cardiomyopathy - Ntinopoulos, Vasileios; Papadopoulos, Nestoras; Odavic, Dragan; Haeussler, Achim; Dzemali, Omer (The Thoracic and Cardiovascular Surgeon, 2021)
Background Controversy exists about left ventricular systolic function recovery after coronary artery bypass grafting in patients with ischemic cardiomyopathy. The aim of this study is to evaluate the temporal evolvement of left ventricular systolic function after coronary artery bypass surgery in patients with ischemic cardiomyopathy.Patients and Methods A total of 50 patients with coronary artery disease and left ventricular ejection fraction (LVEF) ≤35% underwent isolated coronary artery bypass grafting in a single center in the period 2017 to 2019. We performed a retrospective analysis of the echocardiographic and clinical follow-up data at 3 months and 1 year postoperatively.Results Median LVEF preoperatively was 25% (20–33%), mean patient age was 66 ± 8.2 years, 33 (66%) patients were operated off-pump, and 22 (44%) procedures were non-elective. There was no in-hospital myocardial infarction, stroke, and repeat revascularization. Three (6%) patients underwent re-exploration for bleeding or tamponade. In-hospital mortality was 8% and 1-year mortality was 12%. At 1 year postoperatively, there was no repeat revascularization, no myocardial infarction, 1 (2.6%) patient had a transient ischemic attack, and 10 (20%) patients required an implantable defibrillator. There was a statistically significant median ejection fraction increase at 3 months (15% [5–22%], p < 0.0001) and 1 year (23% [13–25%], p < 0.0001) postoperatively, with an absolute increase ≥10% in 32 (74.4%) and 30 (78.9%) patients at 3 months and 1 year, respectively.Conclusion Patients with ischemic cardiomyopathy undergoing coronary artery bypass surgery show continuous recovery of left ventricular systolic function in the first postoperative year.
Keywords: coronary artery bypass grafting; CABG; off-pump surgery; heart failure